IMPLEMENTASI METODE BERMAIN DALAM MENINGKATKAN HASIL BELAJAR IPS DI MADRASAH IBTIDAIYAH - IFRIANTI, SYOFNIDAH (Universitas Islam Negeri Raden Intan Lampung, 2015)
The most important aspect in formal education at school is teaching-learning process. A good process will create a quality and meaningful learning. Organize learning experiences. conduct teaching-learning process. evaluate learning process and result are teacher’s responsibility. One of ways to improve learning achievement is designing a teaching-learning process properly.Game is an alternative method which can be implemented in teaching activity. including Social Science class. Game is a relevant. effective. and appropriate teaching method which can be applied by the teacher especially to develop student’s ability of cognitive. affective. and psychomotor. The implementation of game method will involve the students actively and train the students to know their environment.Social science is a subject with wide coverage which is based on study of economy. geography. sociology. anthropology. governance and history. That is why an appropriate teaching method will influence learning situation to the students. Finally it will also influence the students’ achievement. In the other word. the implementation of game method can help students improve their learning achievement.